Weight sl(3)-modules generated by half-primitive elements - Futorny , V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
Generalized Verma modules over the Lie algebra sl(3, C) that contain no highest vector are studied. Such modules are generated by semiprimitive elements. The composition structure of these modules is studied, an irreducibility criterion is given. Explicit formulas for semiprimitive elements are obtained.